PERBEDAAN FEEDER SPACE TERHADAP PERTAMBAHAN BOBOT BADAN DAN KESERAGAMAN AYAM PETELUR - Naufal, M. Arif; kustanti, nita opi ari; esti, risma novela (Universitas Islam Balitar, 2024)
This study aims to determine the differences in feeder space on weight gain and uniformity of laying hens in the grower phase of the closed house system. The study was conducted in a closed house owned by PT Jatinom Indah Farm with 180 Isa brown chicken strains in Slorok Village, Doko District, Blitar Regency, which began on February 25, 2024 and ended on April 28, 2024. The experiment was conducted using the Posttest-Only Control Design method where the treatment was only in the experimental class and the control class was used for comparison objects. Observations were made after the chickens were 7 weeks to 16 weeks old. The observation parameters included weight gain and uniformity. The results showed that the treatment using different feeder spaces did not show a significant value on the weight gain of laying hens in the grower phase (P> 0.05). With the average result of weight gain of the control class of 82.76 gr and in the experimental class of 82.39 gr. However, the treatment with different feeder space showed a significant value on the uniformity of laying hens in the grower phase (P <0.05). With the average result of uniformity of the control class of 86.94% and in the experimental class of 93.47%.